Financial Socialization, Childhood Experiences and Financial Well-Being: The Mediating Role of Locus of Control - Ullah, Saif; Yusheng, Kong (Frontiers in Psychology, 2020)
The present study evaluates an empirical model of financial well-being (FWB) based on early childhood consumer experiences (ECCE) and financial socialization (FS). FWB is the overall satisfaction with one’s current financial situation, and that plays a vital role in the overall success and helps to overcome psychological health issues among adults. The results of the study suggested that ECCE has a significant direct effect on the FWB among adults. Moreover, FS agents such as peers harm the financial well-being of the adults. The results also revealed that financial locus of control (LOC) mediates the relationship between FS agents such as parents, teachers, and FWB. Surprisingly, FS agent peers and ECCE do not affect the FWB of adults when LOC works as a mediator. Possibly, when adults socialize more with parents and teachers, they often disregard the role of peers. Adults’ belief and confidence in their skills are vital in explaining the above relationships. Educationists and practitioners should focus on improving discussions with parents and teachers about the financial matters that result in improvements in financial well-being. The present study also provides theoretical and practical implications for adults, parents, and policymakers.